2020
DOI: 10.1177/2055207620948996
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the quality and reliability of online health information

Abstract: Background Internet represents a relevant source of information, but reliability of data that can be obtained by the web is still an unsolved issue. Non-reliable online information may have a relevance, especially in taking decisions related to health problems. Uncertainties on the quality of online health data may have a negative impact on health-related choices of citizens. Objective This work consisted in a cross-sectional literature review of published papers on online health information. The two main rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 56 publications
(113 reference statements)
4
77
0
Order By: Relevance
“… 26 , 27 Prior work has found that patients with greater health illiteracy may not completely comprehend and may misuse medications, skip appointments, among other negative effects, which leads to worse healthcare outcomes. 28 While low levels of health literacy have been linked to poorer comprehension of orthopaedic care, it remains unclear what the specific effect of low comprehensibility of OPI might be on patient outcomes in clubfoot care and paediatric orthopaedic care more generally. 29…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 27 Prior work has found that patients with greater health illiteracy may not completely comprehend and may misuse medications, skip appointments, among other negative effects, which leads to worse healthcare outcomes. 28 While low levels of health literacy have been linked to poorer comprehension of orthopaedic care, it remains unclear what the specific effect of low comprehensibility of OPI might be on patient outcomes in clubfoot care and paediatric orthopaedic care more generally. 29…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that telemedicine can enhance and optimize the work of community and hospital pharmacies [112][113][114][115]. It was demonstrated that telemedicine services provided after-hours by pharmacists in three community hospitals without 24-hour pharmacy services led to the improvement of drug safety since prescribing accuracy was verified [116,117]. The telemedicine can help to resolve the medication-related problems such as medication and prescription errors.…”
Section: Virtual Clinical Trialsmentioning
confidence: 99%
“…inaccurate, unsubstantiated or inappropriate) is time-consuming and difficult. 6 Before the Internet, medical practitioners and students relied on librarians as information gatekeepers; for Internet information, many human gate-keepers have been removed. Physicians rely on medical search engines (e.g.…”
Section: Introductionmentioning
confidence: 99%